2010
DOI: 10.1097/ajp.0b013e3181b8cdc8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Miniscalpel-needle Release, Acupuncture Needling, and Stretching Exercise to Trigger Point in Myofascial Pain Syndrome

Abstract: The effectiveness of MSN release for MPS is superior to that of acupuncture needling treatment or self neck-stretching exercises alone. The MSN release is also safe, without severe side effects in treatment of MPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 48 publications
3
78
0
2
Order By: Relevance
“…7,42 AROM exercise cause gentle stretching which reduces subcutaneous tightness by movements of superficial tissues over deep tissues and thus aiding joint movement. 7 Ma and his colleagues 34 compared the effects of miniscalpel-needle release, acupuncture needling, and stretching exercise to trigger point in individuals diagnosed with MPS and did not find improvements in cervical ROM after the two week stretching exercise. In contrast, a randomized controlled trial by Oliveira-Campelo and his team 43 found that stretching produced short and medium term effects on cervical ROM and pressure pain sensitivity in myofascial pain located in the upper trapezius muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,42 AROM exercise cause gentle stretching which reduces subcutaneous tightness by movements of superficial tissues over deep tissues and thus aiding joint movement. 7 Ma and his colleagues 34 compared the effects of miniscalpel-needle release, acupuncture needling, and stretching exercise to trigger point in individuals diagnosed with MPS and did not find improvements in cervical ROM after the two week stretching exercise. In contrast, a randomized controlled trial by Oliveira-Campelo and his team 43 found that stretching produced short and medium term effects on cervical ROM and pressure pain sensitivity in myofascial pain located in the upper trapezius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…7,32 Participants were then provided with advice on correct posture (standing, sitting, sleeping, working) and treatment exercises (AROM, stretching, strengthening and scapular stability exercises for upper trapezius) to carry out at home each day until the completion of final measurement. [33][34][35] For each exercise, the participants were asked to perform one set of 10 reps three times a day. The patients were trained on correct posture and how to undertake exercises by the principal investigator at the end of the first treatment session.…”
Section: Standard Care (Control) Groupmentioning
confidence: 99%
“…Nine of these reported the PPT to be significantly elevated [33,40,41,43,51,64,78,79,83], and one study found no significant PPT increase [50]. Among the 26 studies (74.3%) that assessed the effectiveness of an acupuncture series, 18 (69.2%) showed a PPT increase after treatment [37,38,46,50,52,62,63,68,70,72,74,77,81,82,86,87,91,93] while six studies (23.1%) observed no effect of acupuncture on the PPT [22,27,[47][48][49]96]. The outcome of two studies was rated as unclear, because the analysis was performed by combining data of all groups [44,45].…”
Section: Ppt Assessed In Pain Disordersmentioning
confidence: 99%
“…One article reported a significant change of sensory thresholds after an inert control procedure [24]. All four studies evaluating acupuncture as an add-on treatment reported a significant additional effect [38,46,70,87]. In 48 studies (56.5%) one or several types of sham acupuncture treatments were used as controls.…”
Section: Comparison Of Verum Acupuncture To Inert or Sham-control Promentioning
confidence: 99%
See 1 more Smart Citation